Nonmedical Prescription Drug Use (NMPDU) in the Swedish General Population—Correlates of Analgesic and Sedative Use. (28th January 2015) - Abrahamsson, Tove; Hakansson, Anders
<x xml:space="preserve">Abstract</x> Background: Nonmedical prescription drug use (NMPDU) is a growing problem in many countries. Objectives: The aim of the present study was to report correlates of and compare different subtypes of NMPDU in the Swedish general population. Methods: Data were drawn from a Swedish national household survey conducted in 2008–2009. A stratified sample of 58, 000 individuals aged 15 to 64 was randomly selected, with a response rate of 38.3%. Hierarchical logistic regression analysis was used to compare sociodemographic, substance use, and health correlates of nonmedical analgesic use, nonmedical sedative use, and combined nonmedical use of these two types of prescription drugs. Results: In the final logistic regression model, all three patterns of NMPDU were equally associated with female gender, hazardous alcohol use, habitual smoking and cannabis use, but there were several significant differences in other demographic, health, and drug use correlates between the groups. Conclusions/Importance: Nonmedical use of prescription analgesics, prescription sedatives and combined nonmedical use of these drugs might constitute clinically distinct subgroups of NMPDU. This study is one of few to report correlates of NMPDU from a large, national household survey in a country other than the United States.